Active cool stars and He I 10 830 Å: the coronal connection - Sanz-Forcada, J.; Dupree, A. K. (Astronomy and astrophysics (Berlin), 2008)
Context. The mechanism of formation of the He I 10 830 Å triplet in cool stars has been subject of debate for the last 30 years. A relation between the X-ray luminosity and the He I 10 830 Å flux was found in cool stars, but the dominant mechanism of formation in these stars (photoionization by coronal radiation followed by recombination and cascade, or collisional excitation in the chromosphere), has not yet been established. Aims. We use modern instrumentation (NOT/SOFIN) and a direct measurement of the EUV flux, which photoionizes He I, to investigate the formation mechanism of the line for the most active stars which are frequently excluded from analysis. Methods. We have observed with an unprecedented resolution (R ~ 170 000) the He I 10 830 Å triplet in a set of 15 stars that were also observed with the Extreme Ultraviolet Explorer (EUVE) in order to compare the line strengths with their EUV and X-ray fluxes. Results. Active dwarf and subgiant stars do not exhibit a relation between the EUV flux and the equivalent width of the He I 10 830 Å line. Giant stars however, show a positive correlation between the strength of the He I 10 830 Å absorption and the EUV and X-ray fluxes. The strength of the C IV 1550 Å emission does not correlate with coronal fluxes in this sample of 15 stars. Conclusions. Active dwarf stars may have high chromospheric densities thus allowing collisional excitation to dominate photoionization/recombination processes in forming the He I 10 830 Å line. Active giant stars possess lower gravities, and lower chromospheric densities than dwarfs, allowing for photoexcitation processes to become important. Moreover, their extended chromospheres allow for scattering of infrared continuum radiation, producing strong absorption in He I and tracing wind dynamics.